e-Learning cookbook. TPACK in professional development in higher education - Brouwer, Natasa (Amsterdam University Press, 2013)
Information and communication technology (ICT) makes it possible to bring information to everyone who wants to learn. Rapid advances in technology offer strong support for using ICT in teaching. Online education can intensify and improve students' learning process, and enables us to reach more students than by traditional means. The number of courses and modules being offered online is increasing rapidly worldwide. Although online education can reach more people nowadays and new and challenging learning experiences can be created with it, in the average university course the digital dimension too often remains limited to simply publishing the existing face-to-face course content online. It is crucial that lecturers have and can obtain knowledge about how to design technology-enhanced teaching. Technical advances can be expected to continue in the future, and those who wish to implement educational technology in their own teaching practice must reckon on becoming lifelong learners. This fits the culture of academic teachers perfectly: they are already lifelong learners and creators of new knowledge within their discipline. This book is based on the notion that a lecturer who uses ICT in teaching must learn how to apply his or her knowledge about content, pedagogy and technology in an integrated manner. The idea of integrating these three types of knowledge is based on the TPACK model, which stands for Technological Pedagogical Content Knowledge model. The material for this book was developed in a Dutch higher education innovation project known as MARCHET (Make Relevant Choices in Educational Technology, MARCHET, 2009-2011).